2022
DOI: 10.1186/s40249-022-00941-9
|View full text |Cite
|
Sign up to set email alerts
|

From concept to action: a united, holistic and One Health approach to respond to the climate change crisis

Abstract: It is unequivocal that human influence has warmed the planet, which is seriously affecting the planetary health including human health. Adapting climate change should not only be a slogan, but requires a united, holistic action and a paradigm shift from crisis response to an ambitious and integrated approach immediately. Recognizing the urgent needs to tackle the risk connection between climate change and One Health, the four key messages and recommendations that with the intent to guide further research and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Significant numbers of lives can be protected by investing in early warning systems (Adams et al, 2022) (relevant for extreme weather events and microbial and disease outbreaks), which should include monitoring and evaluation (UNSD, 2022). Population health and health system resilience linked to climate change need to be increased, addressing inequities, to better manage complex and compounding hazards in a systems-based manner (Zhang et al, 2022a(Zhang et al, , 2022b.…”
Section: Insight 3: New Threats On the Horizon From Climate-health In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Significant numbers of lives can be protected by investing in early warning systems (Adams et al, 2022) (relevant for extreme weather events and microbial and disease outbreaks), which should include monitoring and evaluation (UNSD, 2022). Population health and health system resilience linked to climate change need to be increased, addressing inequities, to better manage complex and compounding hazards in a systems-based manner (Zhang et al, 2022a(Zhang et al, , 2022b.…”
Section: Insight 3: New Threats On the Horizon From Climate-health In...mentioning
confidence: 99%
“…The financial sector is thus in an early stage of reckoning with the multifaceted challenges presented by climate change. It also suffers from critical constraints such as data gaps in climate disclosure and metrics as well as analytical tools (In & Schumacher, 2021;OECD, 2021) hindering an orderly transition to low-carbon economies, as evidenced by its lateness in recognizing corporate greenwashing and the related risks for global finance (Baldi & Pandimiglio, 2022;Zhang et al, 2022aZhang et al, , 2022b. One study found no difference in the environmental performance of ESG and non-ESG mutual fund companies (Raghunandan & Rajgopal, 2022), with voluntary ESG disclosure being the only differentiator.…”
Section: Insight 7: Sustainable Finance Practices By Private Sector A...mentioning
confidence: 99%
“…For example, during lockdown periods in China, although there were reductions in concentrations of PM 2.5 , PM 10 , NO 2 , SO 2 , and CO, almost all the concentrations remained higher than the WHO AQGs as listed in Table 1, and the observed concentrations of PM 2.5 and O 3 even increased around Beijing (Wang and Zhang 2020). It should be noted that in addition to the high air pollution emissions, the heavy ambient air pollution over Asia is also attributed to the local meteorological conditions, such as weakened surface wind speed, declined vertical wind shear between the lower and upper troposphere, increased potential temperature difference between 850 and 1,000 hPa, enhanced humidity, and a weakened Asian monsoon (Zhang et al 2014;Li et al 2016;Wang and Zhang 2020). This suggests that achieving AQGs in those countries and regions in the near future will be extremely challenging.…”
Section: Take Immediate Action To Reduce Health Burdenmentioning
confidence: 99%
“…We have stepped into a climate-emergency era in which rapid actions to mitigate climate warming threats have become a top priority for governments around the world. Climate change and air pollution are interconnected and are exerting a combined effect on public health (Zhang et al 2022). Evidence suggests that climate change may deteriorate air quality through altering emissions, reactions, and transport of chemical species as well as stagnant weather conditions, which play an important role in driving air pollution events (Zhang 2017).…”
Section: Policy Integration With Climate Actions Toward Cohealth Bene...mentioning
confidence: 99%
See 1 more Smart Citation